Knowledge management in organizations : 10th International Conference, KMO 2015, Maribor, Slovenia, August 24-28, 2015, Proceedings /: 10th International Conference, KMO 2015, Maribor, Slovenia, August 24-28, 2015, Proceedings. (2015) - Unknown
No abstract available